Differential Gene Transcription in Honeybee (Apis cerana) Larvae Challenged by Chinese Sacbrood Virus (CSBV) - Yi Zhang; Xiu Huang; ZaiFu Xu; RiChou Han; JingHua Chen (Sociobiology)
Honey bees are economically important social insect. They are suffering from all kinds of pathogens, especially the virus. In response to pathogens, different immune pathways such as Toll, Imd, Jak-Stat and RNAi are involved. In the present study, the transcription analysis of 32 immune-related genes from Apis cerana challenged by Chinese sacbrood virus (CSBV), the most widely distributed virus in A. cerana, was carried out by qRT-PCR to provide cues for the antiviral mechanism and the effective control of bee viruses. The expression level of 22 genes were statistically changed, including 11 up-regulated genes (catus-2, lys-2, vir, s3a, mta1, faa, vhdl, co-1-iv, ago-1, ago-3, aub) in which 3 (ago-1, ago-3, aub) were related to RNAi pathway, and 11 down-regulated genes (kenny, pgrp-lc, pgrp-s2, abaecin, lys-1, lys-3, domeless, tepa, mlc, dscam, rpl8) related to Toll, Imd, and Jak-Stat pathways. The results indicated CSBV infection in A. cerana may activate a RNA-based antiviral immunity system. This work constituted the first report, under laboratory conditions, about induction of immune related genes in response to CSBV.